Positive Clinical Benefit on Patient Care, Quality of Life, and Symptoms After Contact Force–Guided Radiofrequency Ablation in Persistent Atrial Fibrillation: Analyses From the PRECEPT Prospective Multicenter Study. (January 2021) - Natale, Andrea; Calkins, Hugh; Osorio, Jose; Pollak, Scott J.; Melby, Daniel; Marchlinski, Francis E.; Athill, Charles A.; Delaughter, Craig; Patel, Anshul M.; Gentlesk, Philip J.; DeVille, Brian; Macle, Laurent; et al.
Abstract : Background: There is limited evidence on the long-term clinical benefits of catheter ablation in patients with persistent atrial fibrillation. Methods: PRECEPT was a prospective, multicenter, single-arm Food and Drug Administration–regulated investigational device exemption clinical study. Patients were followed up to 15 months after ablation. Outcomes included use of antiarrhythmic drugs, rate of cardioversions and cardiovascular hospitalization, Atrial Fibrillation Effect on Quality-of-Life score, and Canadian Cardiovascular Society Severity of Atrial Fibrillation score. Results: A total of 333 enrolled persistent atrial fibrillation patients underwent ablation. The cardioversion rate decreased by 83% at the 9- to 15-month follow-up. Antiarrhythmic drug utilization decreased by 69% at 12 to 15 months post-ablation. The Kaplan-Meier estimate of freedom from cardiovascular hospitalization was 84.2% (95% CI, 80.2%–88.2%) at 15 months. Consistent improvements in mean Atrial Fibrillation Effect on Quality-of-Life composite (+50.0) were seen at 6 months, sustained at 15 months, and exceeded the minimum clinically important difference. Improvements in Atrial Fibrillation Effect on Quality-of-Life scores were significantly better among participants without documented atrial arrhythmia recurrences. By Canadian Cardiovascular Society Severity of Atrial Fibrillation symptom classification, >80% of patients were asymptomatic (class 0) at 15 months post-ablation compared with only 0.7% at baseline. Conclusions: Contact force–guided radiofrequency ablation of persistent atrial fibrillation was associated with a significant decrease in antiarrhythmic drug use, cardioversion rate, and hospitalization. Clinically meaningful improvements in quality of life were observed in all patients. The majority of the patients (>80%) were asymptomatic at 15 months post-ablation. The positive clinical impact of improved quality of life and reduced health care utilization may help with shared decision-making in persistent atrial fibrillation treatment. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02817776. Abstract : Supplemental Digital Content is available in the text.